Evaluation of the role of propolis and a new herbal ointment in promoting healing of traumatic oral ulcers: An animal experimental study - Aditya S Patel; Shraddha A Patel; Puneet R Fulzele; Swapnil C Mohod; Manoj Chandak; Satyawan S Patel (Contemporary Clinical Dentistry, 2020)
Most of the currently used medications for the treatment of oral ulcers focus primarily on providing symptomatic relief and preventing secondary infections. Not much attention has been paid in the past on agents that can promote healing of these lesions. In the current study, we have tested and compared the efficacy of such wound healing promoting agents i.e. Propolis (product obtained from Bees) and a newly developed herbal ointment (containing extracts of Azadirachta indica (Neem), Linum usitatissimum L.(Linseed) oil, and resin of Shorea robusta) in experimental rabbits. Methodology: Traumatic oral ulcers were inflicted in experimental rabbits (New Zealand white) with the help of a punch biopsy instrument. The animals were then divided into three groups each group consisted of 12 animals (n = 12), Group I was the untreated control group and Group II was topically treated with nonalcohol extract of propolis and Group III was treated with newly developed herbal ointment. Histological healing scores of the ulcers were evaluated on day 7 and day 14. Data were statistically analyzed using descriptive and inferential statistic methods. Results: In Group III treated with newly developed herbal ointment, significantly higher healing scores, in comparison to the untreated control group (Group I) and propolis (Group II) was observed on day 7 and 14. Improved healing scores in prapolis-treated group were observed than the untreated control group. However, the difference was not statistically significant on both day 7 and day 14. Conclusion: With the newly developed herbal ointment, superior healing of traumatic oral ulcers was observed.